Mastering the New Testament ; v. 12 - Palmer, Earl F. (Dallas, TX Word, 1982)
Contents : v. 12 : 1,2,3, John, Revelation. Includes bibliographical references.
Keywords: Bible. N.T. Epistles of John -- commentaries; Bible. N.T. Revelation -- commentaries